1998
DOI: 10.1037/0021-843x.107.4.681
|View full text |Cite
|
Sign up to set email alerts
|

Social support predicts 5-year outcome in first-episode schizophrenia.

Abstract: Investigations of social support in schizophrenia have been relatively sparse. In this research, patients with 1st-episode schizophrenia or affective psychosis were asked to describe supportive social relationships immediately prior to their 1st lifetime treatment contact and were interviewed 18 months and 5 years later for assessment of their social and occupational functioning. The results indicated that 18-month adaptive functioning was lower than in the year prior to 1st treatment contact but at 5 years ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 19 publications
5
41
1
Order By: Relevance
“…In addition, high levels of perceived and actual social support reduce one’s negative appraisal, negative reaction, and physiological stress responses to current and potential future stressful events (Cohen and Wills, 1985). For UHR individuals, the stress-buffering hypothesis may serve as a helpful explanatory framework for understanding the associations between social functioning and symptom severity, given some preliminary evidence that social dysfunction may predate symptom presentation (Erickson et al, 1998; Horan et al, 2006) and that poor peer relationships are common in children who will later develop schizophrenia (Meyer et al, 2005). Social relationships may act as a protective factor against the stressful experience of the first manifestation of positive and negative symptoms during the UHR period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high levels of perceived and actual social support reduce one’s negative appraisal, negative reaction, and physiological stress responses to current and potential future stressful events (Cohen and Wills, 1985). For UHR individuals, the stress-buffering hypothesis may serve as a helpful explanatory framework for understanding the associations between social functioning and symptom severity, given some preliminary evidence that social dysfunction may predate symptom presentation (Erickson et al, 1998; Horan et al, 2006) and that poor peer relationships are common in children who will later develop schizophrenia (Meyer et al, 2005). Social relationships may act as a protective factor against the stressful experience of the first manifestation of positive and negative symptoms during the UHR period.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, research shows that people with serious mental illnesses have a smaller (Furukawa, et al, 1999;Lipton, Cohen, Fischer, & Katz, 1981;Pattison, Llamas, & Hurd, 1979;Randolph & Escobar, 1985;Sokolovsky, Cohen, Berger, & Geiger, 1978;Tolsdorf, 1976) and/or less satisfactory (Bengtsson-Tops & Hansson, 2001;Furukawa, et al, 1999;Tolsdorf, 1976) support network. The second category of research has examined the relationship between objective and subjective measures of social support and outcomes related to mental illness (Denoff & Pilkonis, 1987;Erickson, Beiser, & Iacono, 1998;Meeks & Hammond, 2001;Salokangas, 1997;Wojciechowska, Cechnicki, & Walczewski, 2002). The most prominent of these outcomes has been quality of life with research suggesting people with mental illness who report larger or more satisfactory support networks also report better quality of life (Bengtsson-Tops & Hansson, 2001;Hansson et al, 2002;Rudnick & Kravetz, 2001).…”
mentioning
confidence: 98%
“…Research has shown that social support from family and friends can decrease the symptoms and debilitating impact of mental illness on functioning (Albert, Becker, McCrone, & Thornicroft, 1998; Davidson et al, 2001; Erickson, Beiser, & Iacono, 1998; Fisher, 1994; Jacobson & Greenley, 2001; Mead & Copeland, 2000; Ridgway, 2001; Young & Ensing, 1999), help reduce substance use (Alverson, Alverson, & Drake, 2000; Laudet, Magura, Vogel, & Knight, 2000; Mueser, Bellack, & Blanchard, 1992), and enhance activities of daily living for people with dual diagnoses (Bellack & Mueser, 1986; Clark, 1996, 2001; Clark & Drake, 1994). However, developing and maintaining supportive relationships is often difficult for people who are homeless and have dual diagnoses.…”
mentioning
confidence: 99%